2015
DOI: 10.1021/acs.jpcc.5b03408
|View full text |Cite
|
Sign up to set email alerts
|

Functionalization of Silica Nanoparticles and Native Silicon Oxide with Tailored Boron-Molecular Precursors for Efficient and Predictive p-Doping of Silicon

Abstract: Designing new approaches to incorporate dopant impurities in semiconductor materials is essential in keeping pace with electronics miniaturization without device performance degradation. On the basis of a mild solution-phase synthetic approach to functionalize silica nanoparticles, we were able to graft tailor-made boronmolecular precursors and control the thermal release of boron in the silica framework. The molecular-level description of the surface structure lays the foundation for a structure−property rela… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
30
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
7
1
1

Relationship

3
6

Authors

Journals

citations
Cited by 26 publications
(31 citation statements)
references
References 53 publications
0
30
0
Order By: Relevance
“…In that respect, we have demonstrated that the surface chemistry of a silica layer on passivated silicon wafers is analogous to that of high surface area silica nanoparticles and that identical surface species were found upon immobilization of molecules on both supports. 17,18 …”
mentioning
confidence: 99%
“…In that respect, we have demonstrated that the surface chemistry of a silica layer on passivated silicon wafers is analogous to that of high surface area silica nanoparticles and that identical surface species were found upon immobilization of molecules on both supports. 17,18 …”
mentioning
confidence: 99%
“…15,16 MLD has also been explored for other resists such as oxides, which helps minimize contamination from non-dopant species. [17][18][19][20][21] While solution phase processing allows for scalability, the high temperature anneal required for dopant incorporation limits the utility of wet chemistry methods as it limits dopant concentration to its solid solubility in Si and places restrictions on incorporating ultra-doping into traditional semiconductor fabrication processes. To obtain scalable routes to the transformational Si electronic behavior seen in APAM, we need solution phase chemistry processes that work without an anneal, namely processes involving direct Si-dopant chemistries.…”
Section: Introductionmentioning
confidence: 99%
“…To date, most reports focus on studying the influence of surface chemistry used, molecular footprint, and details of capping layer used on the resulting doping levels. [ 18,27–32 ] The application of phenylboronic acid (PBA) monolayers in doping was previously studied, in part, for the formation of sharp p–i–n junctions in SiNWs, [ 17 ] for studying dopant diffusion and activation in SiNWs, [ 33 ] and for dopant patterning. [ 34 ] Herein, a systematic study to understand the impact of oxide cap deposition on the B‐doping by PBA monolayer is presented.…”
Section: Introductionmentioning
confidence: 99%